Modifikasi HMI Dan Program PLC Sebagai Monitoring Debit Aliran Cooling Sistem Mesin Cold Runner 2000CC (20pt) - Yogi Tama Muhammad Ardiyansyah; Ari Kuswantori; Susilawati, Dera (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
This research discusses monitoring the flow rate used as a cooling medium for a cold runner type curing machine which is equipped with a flow sensor and integrated with an Omron PLC and HMI TS1100 to increase production results in the IMD-50 curing machine. This system is designed to monitor and control coolant flow accurately, so as to maintain product quality. Tests were carried out using the Wilcoxon test method to analyze NG data before and after implementing the modification to add the SM7000 IFM floe sensor, to ensure a significant increase in production efficiency and quality. The research results show that the use of the IFM SM7000 floe sensor on a 2000 cc cold runner curing machine and the integration of the Omron PLC and HMI TS1100 significantly improves process control and reduces torn and short mold NG products. In addition, payback period analysis shows that investments in this system can be returned in a relatively short time, making it an economical andeffective solution for the manufacturing industry. Thus, the implementation of this technology not only provides technical benefits but also significant financial benefits for companies.